2017
DOI: 10.3329/dujs.v65i2.54517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Electrochemical Redox Behavior of Co2+ in Acetate Buffer Solution

Abstract: The electrochemical redox behavior of transition metal ion Co2+ at different pH in acetate buffer solution has been investigated using cyclic voltammetry and differential pulse voltammetry at glassy carbon electrode (GCE). In cyclic voltammograms (CVs), Co2+ shows a pair of cathodic and a pair of anodic peak. The peak potential separation and peak current ratio reveals that the redox process of the redox couples, Co2+/Co+ and Co+/Co followed a quasi-reversible behavior and are two step one-electron transfer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Tere was a linear relationship between the square root of the scan rate and the oxidation peak current, which confrmed that the electrooxidation process of CC and RS on NCNTs (2 : 1)/GCE is regulated by the difusion-controlled electrochemical process (Figures 8(c) and 8(d)) [60]. A shift in the oxidation peak potentials to higher potentials with increasing scan rate was attributed to a tendency of the redox process to shift from quasireversible to irreversible [61]. Tis is also because the concentration of the analyte at the surface of the electrode does not vary at high scan rates since the electron transfer rate constant becomes slow with fast scans since more extreme potentials are needed to induce electron transfer [62].…”
Section: Efect Of Scan Ratementioning
confidence: 67%
“…Tere was a linear relationship between the square root of the scan rate and the oxidation peak current, which confrmed that the electrooxidation process of CC and RS on NCNTs (2 : 1)/GCE is regulated by the difusion-controlled electrochemical process (Figures 8(c) and 8(d)) [60]. A shift in the oxidation peak potentials to higher potentials with increasing scan rate was attributed to a tendency of the redox process to shift from quasireversible to irreversible [61]. Tis is also because the concentration of the analyte at the surface of the electrode does not vary at high scan rates since the electron transfer rate constant becomes slow with fast scans since more extreme potentials are needed to induce electron transfer [62].…”
Section: Efect Of Scan Ratementioning
confidence: 67%
“…These cobalt complexes have shown promising catalytic properties in facilitating the production of H 2 through electrochemical reactions. 2 The electrochemical measurements revealed that the oneelectron reduction of complex 1 was reversible and occurred at a potential of -0.55 V vs SCE in CH3CN (as shown in Table 2). The results of these electrochemical studies have demonstrated that both Complex 1 and its derivative exhibit catalytic activity for H 2 evolution.…”
Section: Electrochemical Systemsmentioning
confidence: 97%
“…Therefore these drugs are really helpful for the remedy of acid caused inflammation condition as well as abscesses of the stomach and duodenum, gastroesophageal reflux illness, all produced by stomach acid 6 . Omeprazole is one of the well-known proton pump 7,8 Because of the significance of drugs and their compounds 9 , it is appropriate to make the metal complexes of omeprazole and investigate their properties 10,11,12 . It is likewise recognized that complexes with metal show a crucial function in biological actions of medicine.…”
Section: Introductionmentioning
confidence: 99%